2021
DOI: 10.1097/wnr.0000000000001637
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics alleviate depressive behavior in chronic unpredictable mild stress rat models by remodeling intestinal flora

Abstract: Objective To explore the effects of probiotics on depressive behavior in a chronic unpredictable mild stress (CUMS) rat model by remodeling intestinal flora.Methods Twenty-four male SD rats aged 6-8 weeks were randomly divided into four groups: control group, depression group (CUMS), depression+paroxetine group (Paro) and depression+probiotics group (Pro). Sucrose preference, open field and forced swimming tests were used to assess depression-like behavior in rats. ELISA was used to detect the levels of adreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
(41 reference statements)
0
8
0
Order By: Relevance
“… 176 In the treatment of depression, probiotics reduced chronic unpredictable mild stress‐induced depressive behavior of rats and increased the levels of norepinephrine and 5‐HT and inhibited the expression of adrenocorticotropic hormone and corticosterone. 177 Consistent with this finding, in a clinical depression treatment trial, the symptoms of all clinical trial participants were improved with a significant correlation between Ruminococcus gnavus and depression. 178 Thus, the current findings could consider probiotic development as an adjunct to existing treatments.…”
Section: Intervention Treatment Of Gut Microbiotamentioning
confidence: 52%
See 1 more Smart Citation
“… 176 In the treatment of depression, probiotics reduced chronic unpredictable mild stress‐induced depressive behavior of rats and increased the levels of norepinephrine and 5‐HT and inhibited the expression of adrenocorticotropic hormone and corticosterone. 177 Consistent with this finding, in a clinical depression treatment trial, the symptoms of all clinical trial participants were improved with a significant correlation between Ruminococcus gnavus and depression. 178 Thus, the current findings could consider probiotic development as an adjunct to existing treatments.…”
Section: Intervention Treatment Of Gut Microbiotamentioning
confidence: 52%
“…Probiotics reduced the production of inflammatory factors and induced changes in microbial flora structure and increased the relative abundance of beneficial microorganisms in diabetic rats 176 . In the treatment of depression, probiotics reduced chronic unpredictable mild stress‐induced depressive behavior of rats and increased the levels of norepinephrine and 5‐HT and inhibited the expression of adrenocorticotropic hormone and corticosterone 177 . Consistent with this finding, in a clinical depression treatment trial, the symptoms of all clinical trial participants were improved with a significant correlation between Ruminococcus gnavus and depression 178 .…”
Section: Intervention Treatment Of Gut Microbiotamentioning
confidence: 99%
“…50 In mice lacking intestinal gut microbes associated with restraint stress, there was a significant increase in serum adrenocorticotrophic and corticosterone hormone levels. 51 Furthermore, administration of Lactobacillus rhamnosus (JB-1) attenuated high corticosterone levels induced by swimming stress in mice. 52 Lactobacillus farciminis was found to attenuate HPA axis response to acute stress.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in the Sox2 plays an important role in the development process of the nervous system [34]. It was reported that Sox2 is mainly found in neurons and may possibly play a role in the pathophysiology of epilepsy [34,35]. Heterozygous Sox2 deficiency in humans was reported to cause hippocampal malformation, forebrain abnormalities, and epilepsy [36,37].…”
Section: Discussionmentioning
confidence: 99%